Long‐Term Support Is Needed for Crucial Ground‐Based Sensor Networks - J. L. Gannon; S. Morley; N. Lugaz; H. Liu; B. Carter; S. Zou (Space Weather)
Abstract Recently, many in the space weather community have taken up the cause to advocate for an orphan among our own. It’s an important fight—for ground‐based sensor networks. Although ground‐based sensors are used across all disciplines of space weather, in terms of long‐term support, they have no single clear home in any United States agency or department. This has resulted in an ongoing struggle throughout the community to maintain important space weather sensors and networks.